Effect of Work Motivation, Work Stress and Compensation on Employee Performance at PT Prima Jaya Motorindo - Hendra Nazmi; Richo Steve; Shelly Cristy (Kusuma Negara Business School, 2022)
The purpose of doing this research is to determine the reduced performance of employees of PT Prima Jaya Motorindo caused by work motivation, work stress and compensation. The theory to support the research is the theory according to experts related to work motivation, work stress, compensation and performance. 78 employees were used as the population and at the same time the sample in this study, but for validity and reliability tests were carried out at PT. Capella Medan using 30 workers. The results showed that partially work motivation and compensation had a significant effect on performance, while work stress had no significant effect on employee performance. Work Motivation, Work Stress and Compensation simultaneously have a significant effect on employee performance with a coefficient of determination of 19.7% and the remaining 80.3% is the influence of other independent variables not examined in this study such as training, recruitment, etc.